Effects of testosterone therapy in adult males with hypogonadism and T2DM: A meta-analysis and systematic review. Issue 8 (August 2022) - Kumar, Satesh; Khatri, Mahima; Memon, Rahat Ahmed; Velastegui, Jordan Llerena; Podaneva, Kristina Zumbana; Gutierrez, Daniela Benitez; Nadeem, Bilawal; Anumolu, Akhil Raj; Azhar, Masood; Zain, Ahmad
Abstract: Background and aims: Testosterone supplementation therapy (TST) is a longstanding treatment for hypogonadal men with type 2 diabetes mellitus (T2DM), even though the benefits of TST are variable among trials. This meta-analysis was done to determine the specific role of TST in hypogonadal men with T2DM. Methods: PubMed, Embase, and Google Scholar were queried to discover eligible randomized controlled trials (RCTs) and observational studies. To quantify the specific effects of TST, we estimated pooled mean differences (MDs) and relative risks with 95% confidence intervals (CIs). Results: Our meta-analysis included 1596 hypogonadal T2DM subjects from 12 randomized controlled trials and one observational study. TST can significantly enhance glycemic control compared to placebo by decreasing homeostatic model assessment of insulin resistance (WMD = −1.55 [-2.65, −0.45]; p = 0.26; I2 = 20.2%), fasting glucose (WMD = −0.35 [-0.79, 0.10]; p = 0.07; I2 = 69.7%), fasting insulin (WMD = −2.88 [-6.12, 0.36]; p = In addition, TST can decrease cholesterol (WMD = −0.28 [-0.47, −0.09] p = 0.0008; I2 = 91%) and triglyceride (WMD = −0.23 [-0.43, −0.03] p = 0.03; I2 = 79.2%). Furthermore, Testosterone therapy is related to a significant rise in total testosterone levels (WMD = 5.08 [2.90, 7.26] p = 0.0002; I2 = 92.9%). Pooling of free testosterone levels indicated a larger increase in the patients who got TST than placebo (WMD = 81.21 [23.87, 138.54] p = 0.07; I2 = 70%). Conclusion: Our findings suggested that TST can enhance glycemic control and hormone levels and reduce total cholesterol, triglyceride, LDL cholesterol whereas increase HDL cholesterol in hypogonadal T2DM patients. Therefore, in these patients, we propose TST alongside anti-diabetic treatment. Highlights: Testosterone supplementation therapy (TST) has been used to treat hypogonadal men with type 2 diabetes mellitus (T2DM) for a long time. . TST decreases homeostatic model assessments of insulin resistance, HbA1c, fasting glucose, and fasting insulin. . TST can significantly decrease total cholesterol and triglyceride levels.